Phytochemical Analysis from Three Different Methanolic Extracts of Red Ginger (Zingiber officinale var. Rubrum) Against LC50 Treatment of Zebra Fish as Model Fish - Eka Fitria Febriani; Maheno Sri Widodo; Abdul Rahem Faqih (Department of Aquaculture, 2023)
Red ginger (Zingiber officinale var. Rubrum) as one of the Indonesian spices has so many important roles, especially in the health sector as a medicinal plant, which has many active compounds including phenols, alkaloids, flavonoids, steroids and tannins. From some researches before, we can know that plants which grow in different places or locations have different tolerances generally. That statements can show that they have different content in their constituent metabolites definitely. Therefore, phytochemical analysis is needed to analyze the content of each red ginger (Z. officinale var. Rubrum) from three locations such as Red ginger (Z. officinale var. Rubrum) from Batu, Malang (RGB), Plaosan, Magetan (RGP) and Simalungun, Medan (RGS) to analyze each content its contains. Also, perform LC50 was needed for analyzing its effect on Zebra fish (Danio rerio) as a model fish. For this research, we use an experimental study with a Completely Randomized Factorial Design (CRFD) method that has two independent variable such as different dosage and type of red ginger (Z. officinale var. Rubrum). In this study, from five dosages (10 mg/l; 20 mg/l; 30 mg/l; 40 mg/l; 50 mg/l) and three types of red ginger (Z. officinale var. Rubrum) treatment, it found that the highest mortality and lowest survival rate were at the highest dosage (50 mg/l) in RGB and extreme increase or decrease in the curve is found in RGP treatment.